ANXIETY SYNDROME IN PATIENTS WITH ARTERIAL HYPERTENSION AND OBESITY AND ITS EFFECT ON CARDIOVASCULAR RISK FACTORS - E. I. Panova; A. O. Kovaleva; Y. V. Katynova; E. P. Govorkova (SINAPS LLC, 2018)
Purpose of the study: The aim of the study was to reveal the prevalence of anxiety syndrome in young men (working age) with arterial hypertension (AH), to compare its frequency depending on the presence and absence of obesity (OB), and also to trace its connection with the parameters of left ventricular myocardial remodeling according to echocardiography and with eating behavior. Materials and methods: The examination included 80 patients with AH hospitalized in connection with the deterioration of the course of the disease, as well as for routine examination. Depending on body mass index, all examined patients were divided into 2 groups: 1- with obesity, 2-control. All examinees were questionnaires with questionnaires to identify personal and situational anxiety, as well as various types of eating disorders. Results and discussion: In the course of the study, it was found that the presence of coolant in patients with AH is associated with the inclusion of pathological mechanisms such as anxiety, which in turn lead to the progression of myocardial pathology, in particular myocardial remodeling. It is significant that the anxiety syndrome in OB is directly associated with the restrictive and external type of eating disorders. Conclusion: timely detection of a high level of anxiety, as well as abnormalities in nutritional behavior with OB by testing patients opens up prospects for optimizing treatment using not only medicamental factors, but also psychocorrecting effects.